2017
DOI: 10.3892/ijmm.2017.2874
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis and the concept of 'interstitial fluids hierarchy': Relevance of cerebrospinal fluid sodium concentrations and brain temperature control (Review)

Abstract: In this review, the aspects and further developments of the concept of homeostasis are discussed also in the perspective of their possible impact in the clinical practice, particularly as far as psychic homeostasis is concerned. A brief historical survey and comments on the concept of homeostasis and allostasis are presented to introduce our proposal that is based on the classical assumption of the interstitial fluid (ISF) as the internal medium for multicellular organisms. However, the new concept of a hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…There is however an important exceptionthe brain, where autonomous interstitial fluid is surrounded by tightly packed endothelial barriers [23,35,49]. This allows the ascorbate concentration in interstitial fluids of the brain to be maintained at the level of 0.5 mM [50]. Ascorbate is extracted from interstitial fluids by cells into their cytoplasm by high affinity/low capacity SVCT2 transporters [20,[51][52][53].…”
Section: Physiological Homeostasis Of Vitamin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…There is however an important exceptionthe brain, where autonomous interstitial fluid is surrounded by tightly packed endothelial barriers [23,35,49]. This allows the ascorbate concentration in interstitial fluids of the brain to be maintained at the level of 0.5 mM [50]. Ascorbate is extracted from interstitial fluids by cells into their cytoplasm by high affinity/low capacity SVCT2 transporters [20,[51][52][53].…”
Section: Physiological Homeostasis Of Vitamin Cmentioning
confidence: 99%
“…Secondly, the physiological arrangement of ascorbate transporters ensures its low interstitial ascorbate concentration, thus limiting the risk of generation of a significant quantity of toxic labile transition metals [59,60]. The ascorbate homeostasis in interstitial fluids (deficient in humans) provides a uniform baseline against which all other cells adjust their cytoplasmic concentrations by simply controlling the number of SVCT2 transporters [50]. Therefore, the ascorbate deficiency will affect interstitial compartments first.…”
Section: Significance Of Ascorbate Passive Diffusion Through the Biolmentioning
confidence: 99%
“…Extracellular fluid, especially interstitial fluid (IF), interacts with cells to maintain organ homeostasis [57]. Any alteration of IF composition disturbs the interaction between IF and cells.…”
Section: Cell Densitymentioning
confidence: 99%
“…However, it is possible that drug-induced serum hyponatremia may cause a more severe reduction of extracellular Na þ at the synaptic level. In a recent review, Agnati et al (2017) suggested the existence of local homeostatic differences in the brain interstitial fluid surrounding the neurons, particularly with respect to the concentration of Na þ , finally resulting in lower concentrations in the CSF compared with serum during the circadian rhythm. Thus, it cannot be excluded that drug-induced hyponatremia may eventually become severe enough in synaptic surroundings to facilitate DOM excitotoxicity.…”
Section: Relevance To Hyponatremiamentioning
confidence: 99%